Schistura madhavai, a new species of hill-stream loach from Sri Lanka, with redescription of S. notostigma (Teleostei: Nemacheilidae) - Sudasinghe, Hiranya (Zootaxa, 2017)
Schistura madhavai, new species, is described from Suriyakanda, Sri Lanka. It is distinguished from all other species of Schistura in the peninsula of India and Sri Lanka by the combination of the following characters: 8–9 wide, brown postdorsal bars separated by narrow, white interspaces; width of interspaces ¼–⅓ times width of bars; black bar at caudal-fin base wider than interspaces on the body; incomplete lateral line, ending beneath dorsal-fin base; absence of an axillary pelvic lobe; adpressed pelvic fin just reaching anus; origin of the pelvic fin on a vertical through the last unbranched dorsal-fin ray. Schistura notostigma, the only other Sri Lankan species of Schistura, is redescribed. It can be distinguished from all other species of Schistura in the peninsula of India and Sri Lanka by the combination of the following characters: 6–7 wide, brown postdorsal bars; width of interspaces ½–1 times width of bars; complete, black bar at caudal-fin base narrower than width of interspaces between bars on body; emarginate caudal fin; incomplete lateral line ending beneath dorsal-fin base; adpressed pelvic fin surpassing anus; and origin of pelvic fin beneath first branched dorsal-fin ray. Schistura madhavai is separated from S. notostigma by an uncorrected pairwise distance of 3.0–3.8% for the 16S rRNA gene fragment.